Robot‐assisted laparoscopic vesicule prostatectomy for mixed epithelial–stromal tumor of seminal vesicle. Issue 3 (19th April 2020) - Masuo, Yuki; Taniguchi, Hisanori; Matsuzaki, Tomoaki; Kinoshita, Hidefumi; Miyasaka, Chika; Ohe, Chisato; Matsuda, Tadashi
Abstract : Introduction: Mixed epithelial–stromal tumor is a biphasic tumor with stromal and benign epithelial components. Only 40 cases of mixed epithelial‐stromal tumor originating from a seminal vesicle have previously been published in English. Case presentation: A 52‐year‐old man was transferred to our hospital for evaluation of a 3.0‐cm pelvic tumor detected incidentally by computed tomography. Robot‐assisted laparoscopic vesicle prostatectomy was performed. We approached the Retzius space from both levels of the pouch of Douglas and peritoneal top of the bladder to clarify the tumor's environment. Pathologically, the tumor was diagnosed as a low‐grade mixed epithelial–stromal tumor originating from the right seminal vesicle. There was no evidence of disease recurrence within 51 months. Conclusion: This is the first report of robot‐assisted laparoscopic vesicle prostatectomy for a seminal vesicle mixed epithelial–stromal tumor. Long‐term observation is warranted due to the lack of reports with sufficient follow‐up to ensure the procedure's safety.